2002
DOI: 10.1088/0967-3334/23/4/301
|View full text |Cite
|
Sign up to set email alerts
|

Detection of spatial repolarization abnormalities in patients with LQT1 and LQT2 forms of congenital long-QT syndrome

Abstract: The aim of this study is to detect the spatial current dispersion that appears in the T-wave of patients with congenital long-QT syndrome (LQTS). To observe this dispersion, magnetocardiograms (MCGs)--which have a high spatial resolution--of LQT1 patients (n = 7), LQT2 patients (n = 9) and a control group (n = 33) were recorded. The dispersion was evaluated by plotting current-arrow maps (CAMs) calculated from the MCG signals. In the case of LQT1, abnormal current arrows in the CAMs appeared above the inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…From MCG signals, a great deal of useful information concerning cardiac disease can be obtained: QT and QRS prolongation caused by myocardial abnormalities were studied using the late fields of MCG signals; [1][2][3]25 T wave deviation of MCG signal is used to detecting IHD. [1][2][3]26 These characteristics indicated MCG recording can provide value information for clinicians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From MCG signals, a great deal of useful information concerning cardiac disease can be obtained: QT and QRS prolongation caused by myocardial abnormalities were studied using the late fields of MCG signals; [1][2][3]25 T wave deviation of MCG signal is used to detecting IHD. [1][2][3]26 These characteristics indicated MCG recording can provide value information for clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…Successful results have been reported in clinically relevant applications. [1][2][3][25][26][27][28] Our practical studies can provide 3D imaging, isomagnetic field maps and CMDs at T wave with sufficient spatial resolution. These results are considered as a major argument for IHD.…”
Section: Resultsmentioning
confidence: 99%
“…Kandori et al calculated current arrow maps from MCG signals of fetuses and adults and identified spatial current dispersions in both the QRS complex and T-wave, which could be used to make a prenatal diagnosis and to distinguish between different LQTS forms in adults [47][48][49]. It was also the group around Kandori who used a whole-heart electrical-activation diagram (W-HEAD) model for visualization of the spatial time-variant activation of the whole heart.…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 99%
“…A two-dimensional (2-D) current-arrow map (CAM) [13] has been proposed as a method for calculating pseudo-cardiac electrical current from MCG signals. Maps of this type are providing the basis for a new method of analyzing atrial excitation of normal subject [14], arrhythmia [15,16] and ischemic heart disease [17]. Furthermore, multiple activated regions during the ventricular depolarization have been visualized by using the anterior and posterior CAMs [18].…”
Section: Introductionmentioning
confidence: 99%